The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1136/adc.87.4.320
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones before and after weight loss in obesity

Abstract: Background: Little is known about changes in thyroid function in obese children. An influence of leptin on thyroid hormone synthesis has been proposed. Aims: To examine thyroid function and leptin concentrations in obese children. Methods: Triiodothyronine (T3), thyroxine (T4), thyroid stimulating hormone (TSH), and leptin were measured in 118 obese children (aged 4.5-16 years); thyroid function was also determined in 107 healthy children of normal weight. T3, T4, and TSH were analysed in 55 obese children who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
182
6
27

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(238 citation statements)
references
References 23 publications
23
182
6
27
Order By: Relevance
“…The observation of elevated plasma sOB-R levels concentrations in children (Kratzsch et al, 2002) and the increased BL fraction, here reported, may contribute to the temporary blockade of the reproductive axis in prepubertal children, which may be overcome, once an increase of FL occurs, in association with an increased adiposity and possibly other factors, giving rise to pubertal development. No relationship between thyroid function and leptin concentrations were found in DS children, as also shown in subjects with congenital hypothyroidism (Asami et al, 2000) and obesity (Reinehr & Andler, 2002), whereas an inverse correlation between leptin and TSH was found in normal children of short stature (Ghizzoni et al, 2001). These discrepancies are similar to those observed in adults with or without thyroid diseases (Corbetta et al, 1997;Valcavi et al, 1997;Korbonits, 1998).…”
Section: Discussionsupporting
confidence: 60%
“…The observation of elevated plasma sOB-R levels concentrations in children (Kratzsch et al, 2002) and the increased BL fraction, here reported, may contribute to the temporary blockade of the reproductive axis in prepubertal children, which may be overcome, once an increase of FL occurs, in association with an increased adiposity and possibly other factors, giving rise to pubertal development. No relationship between thyroid function and leptin concentrations were found in DS children, as also shown in subjects with congenital hypothyroidism (Asami et al, 2000) and obesity (Reinehr & Andler, 2002), whereas an inverse correlation between leptin and TSH was found in normal children of short stature (Ghizzoni et al, 2001). These discrepancies are similar to those observed in adults with or without thyroid diseases (Corbetta et al, 1997;Valcavi et al, 1997;Korbonits, 1998).…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, this study is one of the few investigations that have unequivocally shown that weight loss leads to a reduction in both TSH and FT 3 levels. 9,10,19,20 Several explanations have been proposed to account for the influence of obesity on thyroid hormones. One suggests that the increased TSH level could reflect pituitary adaptation to increased adiposity through adipokines.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is possible that obesity leads to a state of TSH and thyroid hormone resistance in peripheral tissues. 20 However, information on the tissue expression of genes encoding for TSH and thyroid hormone receptors, and activity of the respective proteins in relation to body weight or diabetes is scarce. TSHRs have been found in rats and in human adipose tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A slight increase in TSH levels has been reported in adults with moderate obesity and in obese Pituitary hormones and bariatric surgery S Camastra et al children. 17,38,39 In rodents, leptin modulates thyroid hormone production in situations in which energy conservation through a reduction in metabolic rate is required. 40 Such effect appears to occur principally at the level of TRH neurons in the paraventricular hypothalamic nucleus (PVN).…”
Section: Discussionmentioning
confidence: 99%